2005
DOI: 10.3168/jds.s0022-0302(05)72861-7
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding in Danish Dairy Cattle Breeds

Abstract: The purpose of this study was to monitor current and predict future rates of inbreeding in the Danish dairy breeds. Calves born from 1999 until 2003 and registered as Danish Holstein (1,883,983), Danish Jersey (336,966), or Danish Red (261,047) were reference populations. Average complete generation equivalent was approximately 7. For calves born in 2003, average inbreeding was 3.9, 3.4, and 1.4% for Holstein, Jersey, and Danish Red, respectively. In recent years, effective population sizes were 49, 53, and 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
196
16
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(244 citation statements)
references
References 19 publications
25
196
16
7
Order By: Relevance
“…The PCI of the GCN in this study was comparable to the values reported for Danish dairy cattle breeds, 94% on average (Sørensen et al, 2005). The GSA and GUS showed relatively lower completeness.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The PCI of the GCN in this study was comparable to the values reported for Danish dairy cattle breeds, 94% on average (Sørensen et al, 2005). The GSA and GUS showed relatively lower completeness.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, an effective size of 47 in Canadian Jersey breed, in recent years (2003 to 2007) was reported (Stachowicz et al, 2011). Moreover, the effective population sizes of three Danish dairy breeds were within or below the range of 50 to 100 (Sørensen et al, 2005), which was mentioned to be the recommended size for livestock breeds. Small effective population size and an increasing inbreeding coefficient will lead to lower genetic diversity in the future.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The start of national genetic evaluations in many European countries dates back to the 1980s, which witnessed a rising rate of exchange of the genetic material. The effective population size of the Brown Swiss population from 1995 onwards was above the recommended effective population size, that is, between 50 and 100 animals (Food and Agriculture Organization of the United Nations, 1998; Bijma, 2003;Sorensen et al, 2005). It should be noted, however, that the recommended number was based on the assumption that natural selection cancels out inbreeding depression (Sorensen et al, 2005).…”
Section: Discussionmentioning
confidence: 95%